Beam characterization by means of emission spectroscopy in the ELISE test facility. (4th April 2017) - Barbisan, M; Bonomo, F; Fantz, U; Wünderlich, D
Abstract: The ELISE (extraction from a large ion source experiment) test facility at IPP Garching hosts a RF H − / D − ion source and an acceleration system. Its target is to demonstrate the performance foreseen for the ITER neutral beam injector (NBI) system in terms of extracted current density ( H / D ), fraction of co-extracted electrons and pulse duration. The size of the ELISE extraction area is half that foreseen for the ITER NBI. This paper presents a detailed study of the ELISE beam divergence and uniformity. In particular, it was possible to describe the beam as the sum of two components at very different divergence: about 2° versus 5° ÷ 7°. As test cases, the beam properties have been measured as function of two source parameters. The first one is the current flowing through the grid facing the plasma, the plasma grid (PG), in order to generate the magnetic filter field. The second one is the bias current flowing between the PG and the source walls. Both the filter field and the bias current influence the fraction of co-extracted electrons, but also the properties of the plasma just in front of the extraction system and the beam properties. The divergence and the uniformity of the beam have been measured by a beam emission spectroscopy (BES) diagnostic; the detailed analysis of the raw spectra collected by BES led to describing the beam with two components of different divergence. This concept has been supported by the information given by thermal imaging of the diagnostic calorimeter. Further support to the proposed beam model has been found in the behavior of the currents flowing in the acceleration system and beamline components; these currents are given by the most divergent (charged) particles of the beam.